2021
DOI: 10.20944/preprints202107.0030.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA Interference and CRISPR/Cas Gene Editing for Crop Improvement: Paradigm Shift Towards Sustainable Agriculture

Abstract: With the rapid population growth, there is an urgent need for innovative crop improvement approaches to meet the increasing demand for food. Classical crop improvement approaches involve, however, a backbreaking process that cannot equipoise with increasing crop demand. RNA based approaches i.e. RNAi-mediated gene regulation and site-specific nuclease based CRISPR/Cas9 system for gene editing has made advances in the efficient targeted modification in many crops for the higher yield and resistance to diseases … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…RNA molecules perform several important tasks in cells, such as transporting genetic information (rRNA -reading the genetic code, and tRNA, protein synthesis). Contrary to what was thought, recently several studies [5][6][7][8][9][10][11] have demonstrated the importance that non-coding RNAs have in the performance of numerous genome protection functions against viruses and transposable elements but also in the regulation of gene expression. Some of these newly discovered RNAs will be discussed throughout the introduction of the thesis.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…RNA molecules perform several important tasks in cells, such as transporting genetic information (rRNA -reading the genetic code, and tRNA, protein synthesis). Contrary to what was thought, recently several studies [5][6][7][8][9][10][11] have demonstrated the importance that non-coding RNAs have in the performance of numerous genome protection functions against viruses and transposable elements but also in the regulation of gene expression. Some of these newly discovered RNAs will be discussed throughout the introduction of the thesis.…”
Section: Introductionmentioning
confidence: 87%
“…Finally, the use of CRISPR raises ethical questions, particularly regarding its use in human cells (germ cells and embryos) [5,6,29,30].…”
Section: Rnai Comparison With Crisprmentioning
confidence: 99%
See 1 more Smart Citation